The reparative spaces of radio. (1st April 2013) - Bainbridge, Caroline; Yates, Candida
This introduction contextualizes the work included in this special edition in terms of the activities of the Media and the Inner World research network. Drawing on object relations psychoanalysis, it signals the importance of the reparative, emotional work of radio past and present. As we discuss, the emotional resonance of the medium holds a special significance for individuals, for whom radio listening often goes hand in hand with reflective experiences of selfhood and identity. The role of radio is also discussed in relation to our emotionalized experience of popular culture and the world at large and the shaping of shared identities and 'imagined communities'. We argue that the social and political function of radio arguably hinges on the psychological power it has because of its status as an important internal object of the mind.